Clinical and Molecular Analysis in Patients with Peutz-Jeghers Syndrome - Günay Aslan, Pınar; Çağlayan, Ahmet Okay; Bora, Elçin; Koç, Altuğ; Yucel, Hilal; Ülgenalp, Ayfer; Öztürk, Yeşim; Şeker, Gül; Akarsu, Mesut (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Peutz–Jeghers syndrome (PJS) is a rare hereditary disorder linked to increased cancer risk due to specific genetic variants in the STK11 gene. This study aimed to assess disease manifestations, genetic profiles, and genotype–phenotype correlations in PJS patients. Materials and Methods: Twenty patients from 14 families with PJS who were followed up at our clinic between 2011 and 2021 were included. Genetic susceptibility to hereditary cancers was assess–ed using targeted next-generation sequencing (NGS) and multiplex ligation-dependent probe amplification (MLPA) of the STK11 gene. Clinical data were also collected and analyzed in conjunction with the genetic findings. Results: Initial symptoms appeared around 18.9 years, predominantly abdominal pain and intussusception. Mucocutaneous lesions were found in 85%, and hamartomatous polyps in 90%. Dysplastic polyps were found in 4 patients, with 3 cases of malignancy. Nextgeneration sequencing identified 11 pathogenic and 3 likely pathogenic mutations, including 3 novel STK11 variants (LRG_319: c.598- 8_601del, LRG_319: c.708_718del, and LRG_319: c.146_147del). Next-generation sequencing diagnostic rate was 78.5% (11/14), and the overall diagnostic rate with NGS and MLPA studies was 85.7% (12/14). Patients without STK11 mutations had later symptom onset and potentially lower cancer risk. Truncated mutations are associated with earlier symptoms and elevated cancer risk. Conclusion: This is the first PJS case series in Turkey using the NGS and MLPA methods. It reports 3 novel mutations and emphasizes the genotype–phenotype relationship of PJS. With further studies, the genotype–phenotype relationship of STK11 variants will be better understood. Cite this article as: Günay Aslan P, Çağlayan AO, Bora E, et al. Clinical and molecular analysis in patients with peutz–jeghers syndrome. Turk J Gastroenterol. 2024;35(5):374-384.